Nonlocal effects in the 8Be breakup - Galetti, D. [UNESP]; Mizrahi, Salomon S.; Chamon, L. C.; Pereira, D.; Hussein, M. S.; Cândido Ribeiro, M. A. (American Physical Soc, 1998)
A collective Hamiltonian for a two alpha particles aggregate, which describes the 8Be nucleus, encompassing a collective potential and an inertia function of that system, is obtained and analyzed through the use of a technique - derived from an approach of the generator coordinate method (GCM) - which allows for the extraction of collective information. The nucleon-nucleon interaction considered here is the one proposed by Volkov plus the Coulomb repulsion. It is shown that nonlocal effects appear in those collective functions describing the spontaneously occurring breakup process. Furthermore, the result for the inertia function stands for a microscopically generated evidence supporting a double-folding-based model of the real part of the nucleus-nucleus nonlocal interaction recently proposed.